2012
DOI: 10.1074/jbc.m112.420869
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis ESAT-6 Exhibits a Unique Membrane-interacting Activity That Is Not Found in Its Ortholog from Non-pathogenic Mycobacterium smegmatis

Abstract: Background: Mycobacterium tuberculosis ESAT-6 (MtbESAT-6) is required for phagosomal rupture and bacterial cytosolic translocation.Results: MtbESAT-6 underwent a pH-dependent conformational change and induced leakage of membrane vesicles, while its ortholog from non-pathogenic Mycobacterium smegmatis, MsESAT-6, did not. Conclusion: MtbESAT-6 possesses a unique membrane-interacting activity that is not found in MsESAT-6. Significance: This study links membrane-interacting activity of ESAT-6 to virulence of M. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
177
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(200 citation statements)
references
References 35 publications
22
177
0
Order By: Relevance
“…The transcription of the early secreted antigenic target 6 kDa protein (ESAT-6) protein secretion system for the export of EsxA and EsxB was activated in the ΔfakA strain (Table S2). The ESAT-6 system is best known in Mycobacterium tuberculosis where the secreted components are involved in the escape from phagocytic compartment into the cytosol (14). EsxA and EsxB are also involved in S. aureus virulence, although the mechanism is not established (15).…”
Section: [ 14 C]fas To the Two Fakbsmentioning
confidence: 99%
“…The transcription of the early secreted antigenic target 6 kDa protein (ESAT-6) protein secretion system for the export of EsxA and EsxB was activated in the ΔfakA strain (Table S2). The ESAT-6 system is best known in Mycobacterium tuberculosis where the secreted components are involved in the escape from phagocytic compartment into the cytosol (14). EsxA and EsxB are also involved in S. aureus virulence, although the mechanism is not established (15).…”
Section: [ 14 C]fas To the Two Fakbsmentioning
confidence: 99%
“…It was hypothesized that this process might be pH dependent (147), but it remains unclear if other factors are also involved, because the data obtained from spectroscopic analyses of recombinant ESAT-6 and CFP-10 preparations predicted stability of the complex even under low pH conditions (148). However, a recent study suggested that there were differences among ESAT-6 orthologs from pathogenic and nonpathogenic mycobacterial species in their ability to undergo a conformational change under acidic pH conditions (149). Furthermore, it is not known whether other proteins co-secreted by ESX-1 might also contribute to membrane perforation.…”
Section: Mycobacterial Systems Discovered By Genomics That Are Involvmentioning
confidence: 99%
“…The heterodimer was shown to dissociate under acidic conditions, hypothetically inside acidic compartments of the macrophage [59]. On the contrary, studies using recombinant ESAT6 and CFP10 expressed in Escherichia coli failed to detect complex dissociation at acidic pH [60,61]. This discrepancy between native and recombinant proteins could be explained by mycobacterium-specific post-translational modifications on ESAT6 [52].…”
Section: Transport Across Membranes Esx-1 Secretion and Esat6mentioning
confidence: 95%
“…This discrepancy between native and recombinant proteins could be explained by mycobacterium-specific post-translational modifications on ESAT6 [52]. Both recombinant and native ESAT6 lyse artificial membranes [59,[61][62][63][64] due to a hypothetical conformational change of ESAT6 that also facilitated membrane interaction [61]. The helix-turn-helix structure of ESAT6 was shown to insert into membranes upon acidification and to form a membrane-spanning structure, which could lead to membrane lysis [65].…”
Section: Transport Across Membranes Esx-1 Secretion and Esat6mentioning
confidence: 99%
See 1 more Smart Citation